Medicinal Plants and its Utility - (:unkn) unknown (Odisha State Nodal Agency Centre for Environmental Studies, 2022)
The book is about the uses and benifits of medicinal plants.
Keywords: Odia; Medicinal Plants and its Utility; Environmental Science; Odia; Odia